The Indian Corporate Board Efficiency and its Impact on Financial Performance - Sarim, Mohd (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of the study is to explore the board characteristics and its impact on the ﬁnancial performance of Indian companies. The sample comprises of top 100 companies listed on the Bombay Stock Exchange for the financial year 2018-2019. The data required for the analysis was collected from the annual reports of the companies available at their respective websites and from the Prowess database of the Centre for Monitoring of Indian Economy. The paper constructed sub-indices for the board as board composition index, board independence index and board disclosure index. Combining all sub-indices, we formed the Board Composite Index. Further, the data was analysed to draw meaningful conclusions. Firm size is used as a controlling variable. The results show that there is a strong relationship between board indicators and return on asset.